Respuesta :

If you want the answer in point slope form then,

y-y1 = m(x-x1)
y-c = m(x-a)

---------------------------------------

If you want the answer in slope intercept form, then solve for y

y-c = m(x-a)
y-c = mx-ma
y-c+c = mx-ma+c
y = mx-ma+c
y = mx+c-ma
y = mx+(c-ma)

For this answer in slope intercept form the slope is m and the y intercept is c-ma

---------------------------------------

If you want the answer in standard form, then get the variable terms to the left side. Have the constant terms on the right side.

y = mx+c-ma
y-mx = mx+c-ma-mx
-mx+y = c-ma

Optionally you can multiply both sides by -1 to get mx-y = -c+ma but it will depend on your book if this step is carried out or not.